Obstructive sleep apnoea associated with syringomyelia. Issue 810 (April 1993) - Ellis, C.; Curzen, N.; Katifi, H.
Abstract : We present a case of obstructive sleep apnoea in association with syringomyelia. We describe the successful treatment of the respiratory obstruction by continuous positive airway pressure and then by surgical means. This rare combination of conditions and the management is reviewed.